Implementation of Good Governance Policy in Village Financial Management - Sudrajat, Arip Rahman (Jurnal Sosial Sains dan Komunikasi, 2023)
The description of the execution of village financial management and the adoption of the principles of good governance is the goal of this study. The location of the research is at Wanguk Village, which is located in the Anjatan District of the Indramayu Regency. The research approach utilized in this investigation is known as qualitative descriptive research. According to the findings, village financial management consisted of the following five stages: planning in accordance with the medium-term work plan and the work plan of the village government; budgeting, the output of which was in the form of village income and expenditure budgets; implementation and administration; reporting that was submitted to the regent every semester; and good accountability to the community and the district head at the end of each fiscal year. Regarding the application of good governance in the administration of village finances in Wanguk Village, viewed from the perspectives of accountability, transparency, and responsiveness, while it has been operating, it is not yet functioning at its full potential.